Immunobiology of Cervix Ripening - Yellon, Steven M. (Frontiers in Immunology, 2020)
The cervix is the essential gatekeeper for birth. Incomplete cervix remodeling contributes to problems with delivery at or post-term while preterm birth is a major factor in perinatal morbidity and mortality in newborns. Lack of cervix biopsies from women during the period preceding term or preterm birth have led to use of rodent models to advanced understanding of the mechanism for prepartum cervix remodeling. The critical transition from a soft cervix to a compliant prepartum lower uterine segment has only recently been recognized to occur in various mammalian species when progesterone in circulation is at or near the peak of pregnancy in preparation for birth. In rodents, characterization of ripening resembles an inflammatory process with a temporal coincidence of decreased density of cell nuclei, decline in cross-linked extracellular collagen, and increased presence of macrophages in the cervix. Although a role for inflammation in parturition and cervix remodeling is not a new concept, a comprehensive examination of literature in this review reveals that many conclusions are drawn from comparisons before and after ripening has occurred, not during the process. The present review focuses on essential phenotypes and functions of resident myeloid and possibly other immune cells to bridge the gap with evidence that specific biomarkers may assess the progress of ripening both at term and with preterm birth. Moreover, use of endpoints to determine the effectiveness of various therapeutic approaches to forestall remodeling and reduce risks for preterm birth, or facilitate ripening to promote parturition will improve the postpartum well-being of mothers and newborns.